2015
DOI: 10.1530/rep-14-0369
|View full text |Cite
|
Sign up to set email alerts
|

GATA4 knockdown in MA-10 Leydig cells identifies multiple target genes in the steroidogenic pathway

Abstract: GATA4 is an essential transcription factor required for the initiation of genital ridge formation, for normal testicular and ovarian differentiation at the time of sex determination, and for male and female fertility in adulthood. In spite of its crucial roles, the genes and/or gene networks that are ultimately regulated by GATA4 in gonadal tissues remain to be fully understood. This is particularly true for the steroidogenic lineages such as Leydig cells of the testis where many in vitro (promoter) studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 75 publications
3
37
0
Order By: Relevance
“…These promoters are synergistically activated by GATA4 and SF-1 (Tremblay and Viger, 2001a, b; Bouchard et al , 2005; Martin et al , 2005; Kwintkiewicz et al , 2007; Schrade et al , 2014; Bergeron et al , 2015). Interestingly, GATA4 activity is negatively regulated by HEY2 in the heart and developing cardiovascular system, making it a possible target for Notch signaling in gonadal cells also (Kathiriya et al , 2004; Kokubo et al , 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These promoters are synergistically activated by GATA4 and SF-1 (Tremblay and Viger, 2001a, b; Bouchard et al , 2005; Martin et al , 2005; Kwintkiewicz et al , 2007; Schrade et al , 2014; Bergeron et al , 2015). Interestingly, GATA4 activity is negatively regulated by HEY2 in the heart and developing cardiovascular system, making it a possible target for Notch signaling in gonadal cells also (Kathiriya et al , 2004; Kokubo et al , 2005).…”
Section: Resultsmentioning
confidence: 99%
“…GATA4 is expressed in both Leydig and granulosa cells (Heikinheimo et al ., 1997; Tremblay and Viger, 2001a, b; Laitinen et al ., 2000; Viger et al ., 1998; 2004; Martin et al ., 2005; Padua et al ., 2014; 2015) and is a key positive transcriptional regulator of genes involved in steroid biosynthesis, including SF-1 ,, Cyp19a1 , Star , 3B hydroxysteroid dehydrogenase (Hsd3b1) , and Cyp11A1 (Wooten-Kee and Clark, 2000; Tremblay and Viger 2001a, b; Tremblay et al ., 2002; Bouchard et al, 2005; Martin et al, 2005; Schrade et al, 2015; Bergeron et al ., 2015). Notch signaling has been demonstrated to inhibit GATA factor mediated transactivation of cardiac, hematopoietic, and skeletal muscle specific promoters (Kathiriya et al ., 2004; Fischer et al ., 2005; Ishiko et al ., 2005; Shirvani et al ., 2006), indicating that the steroidogenic promoters could also be targets of the Notch pathway.…”
Section: Introductionmentioning
confidence: 99%
“…For example, silencing of Gata4 in Leydig tumor cell lines (MA-10, mLTC-1) and primary adult Leydig cells has been shown to impair the expression of androgen biosynthetic genes ( Cyp11a1 , Hsd3b1 , Cyp17a1 ) (Bergeron et al 2015, Schrade et al 2015). In keeping with these prior reports, we found that adenovirus-mediated deletion of Gata4 / 6 in adult Leydig cells caused the acute downregulation of genes involved in sex steroid production, whereas expression of another Leydig cell marker, Insl3 , was preserved at early time points.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the SREBP2-regulated genes Hmgcr, Fdps, Cyp51, and Ldlr were all significantly up-regulated by the PDE inhibitors in both WT and SCAP-deficient cells, although the absolute levels were lower in SCAP-deficient cells. Some portion of these effects could be due to PKA-mediated activation of the transcription factors CREB, SF-1 (Nr5a1), GATA4, and NF-γ/p300, because maximal transcriptional activation by SREBPs requires activation of multiple transcription factors (38)(39)(40)(41). In addition to the facilitation of cholesterol biosynthesis, the up-regulation of Hmgcr and Fdps by PKA should also increase the availability of isoprenoids that are necessary to locate small GTPases to their proper targets.…”
Section: Discussionmentioning
confidence: 99%